Perceived acceptability, barriers and enablers in implementing mobile phone messaging-based message-framing intervention for improved maternal and newborn care in Jimma Zone, Ethiopia: a qualitative study - Gebeyehu Bulcha; Zewdie Birhanu; Demisew Amenu; Hordofa Gutema (BMJ Open)
Objective To explore the perceived acceptability, barriers and enablers in implementing mobile phone messaging-based message-framing interventions to improve maternal and newborn care in Jimma Zone, Ethiopia.Design A qualitative study employing thematic analysis of data collected through in-depth interviews (IDIs) and key informant interviews (KIIs).Setting The study was conducted in Dedo, Shabe Sombo and Manna districts of Jimma Zone.Participants We conducted 12 IDIs and 14 KIIs with pregnant women, male partners, health extension workers, healthcare providers and Ethio-Telecom experts across the three districts. Thematic analysis was used to identify patterns and themes in the data.Intervention Mobile phone messaging-based interventions using gain-framed and loss-framed messages were explored for their potential to promote maternal and newborn health practices.Key areas of exploration The study explored participants’ awareness, perceived relevance, acceptability, and barriers and enablers, as well as participants’ engagement with mobile health messaging interventions.Results Participants were generally aware of the potential benefits of mobile phone messaging for maternal and newborn health. Mobile phone-based messaging was perceived as highly relevant and useful by most participants. However, many had limited prior experience using mobile messaging for health information. Despite this, participants expressed a strong willingness and readiness to receive and actively engage with the maternal and newborn mobile messaging intervention. The study also identified various barriers and enablers affecting the implementation of message-framing interventions through mobile phone messaging.Conclusions Participants in this study generally recognised and accepted the benefits of mobile phone messaging for improving maternal and newborn health. Although rural women faced challenges in reading and understanding short messages, they demonstrated a strong willingness to engage with mobile health messaging interventions. The identified barriers were categorised as technological, social, cultural, behavioural and contextual. To maximise the impact of mobile health messaging and ensure broad and effective reach, it is crucial to address these barriers while leveraging existing enablers.Trial registration number This study was conducted as part of a larger cluster randomised controlled trial at Clinical trials PACTR202201753436676, 4 January 2022.